Deep-learning and graph-based approach to table structure recognition - Lee, Eunji; Park, Jaewoo; Koo, Hyung Il; Cho, Nam Ik (Multimedia Tools and Applications, 2022)
Table structure recognition is a key component in document understanding. Many prior methods have addressed this problem with three sequential steps: table detection, table component extraction, and structure analysis based on pairwise relations. However, they have limitations in addressing complexly structured tables and/or practical scenarios (e.g., scanned documents). In this paper, we propose a novel graph-based table structure recognition framework. In order to handle complex tables, we formulate tables as planar graphs, whose faces are cell-regions. Then, we compute vertex (junction) confidence maps and line fields with the heatmap regression networks having a small number of parameters (about 1M) and reconstruct tables by solving a constrained optimization problem. We demonstrate the robustness of the proposed system through experiments on ICDAR 2019 dataset and on challenging table images. Experimental results show that the proposed method outperforms the conventional method for a range of scenarios and delivers good generalization performance.
Keywords: Component extraction; Deep learning; Document understanding; Documents analysis; Graph-based; Graph-based approach; Structure recognition; Table detection; Table structure; Table understanding; Deep learning; Document analysis; Graph-based approach; Table understanding